OPTIMALISASI TENUN SARUNG GOYOR TRADISI SURAKARTA IMPLEMENTASINYA PADA INTERIOR SEBAGAI UPAYA PENGUATAN BUDAYA LOKAL - Muh. Arif Jati Purnomo; Joko Budiwiyanto; FP Sri Wuryani (Pendhapa, 2012)
The study, entitled â€œThe Optimizing of Surakarta Traditional Batik, The Implementationin Tradition-Based Accessories as strengthening efforts Surakarta Local Culture in the Global Eraâ€ to analyze and embodies Surakarta traditional batik as one of the mainstays of traditional souvenirs can be adaptable to support regional tourism and strengthening the local culture in the globalization era. A problem in the study is the lack of optimal utilization Surakarta batik as the souvenirs objects of tourist destination. The Weak sensitivity of craftsmen to the cultural wealth of the archipelago in Surakarta, in particular batik, is seen as a serious problem in an effort to optimize the Surakarta traditional batik. Identification analysis of Surakarta batik used as the indicator of first year performance to find solutions maps of design offer. Experiments conducted in ISI Surakarta by involving the team with the craftsmen. The method used in the first year using the method of content analysis, observation, interviews, experimental design with hermeneutic approach supported by a design, proposed by social, cultural, and psychological approach. The location is done in Surakarta. Data sources include the results of the work, which is a typical batik in Surakarta, informants, cultural figure, craftsmen, the general public, and literature related to the problem. Data collection technique is the study of literature, observations, and interviews. The validity of the data by using triangulation data and the analysis is the interactive analysis model to see the meaning behind the work of design objects. In the analysis phase of design formulation will using SWOT analysis. The focus of the second year of activities such as experimentation, education and training of craftsmen, try out, exhibition and sale of works of accessories, evaluation, refinement and accessories design concept, formulation of recommendations.